2010
DOI: 10.1111/j.1600-9657.2010.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined technique with dentin post reinforcement and original fragment reattachment for the esthetic recovery of a fractured anterior tooth: a case report

Abstract: This case report describes the esthetic and functional recovery of a maxillary central incisor. The treatments used were dentin post (biological post) reinforcement and reattachment of the fragment. From the outcomes achieved, it can be concluded that this technique is promising and is yet another alternative method that can be used for the recovery of fractured anterior teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…elastic modulus, viscoelastic performance, compressive strength, and thermal expansion) (2,6,14). Dentin posts have also presented higher fracture strength and favorable fracture patterns under static and dynamic loading when compared to fiber posts, in addition to appropriate bonding at the post-cement-dentin interface (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…elastic modulus, viscoelastic performance, compressive strength, and thermal expansion) (2,6,14). Dentin posts have also presented higher fracture strength and favorable fracture patterns under static and dynamic loading when compared to fiber posts, in addition to appropriate bonding at the post-cement-dentin interface (2).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have used human teeth for the fabrication of an intracanal retainer, referred to as a "dentin post" (2,6,7). Recent studies have suggested that a dentin post enhances stability and adhesion, which reduces the risk of fracture of endodontically treated teeth (2,6). However, additional studies are necessary for biomechanical evaluation of this material and standardization of the technique for professional use.…”
Section: Introductionmentioning
confidence: 99%
“…A few reported cases utilizing dentin as post material have shown successful outcomes. [45] Hence, the probability of human dentin to serve as a post material needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Kökler 14 mm olacak şekilde koronal kısımlarından su soğutması altında elmas fissür frezlerle aşındırıldı ve bütün kökler aynı boyuta getirildi. Gates glidden frezleri (Mani, Tochigi, Japan) yardımıyla kanal ağızları genişletildi ve endo motor (Dentsply, De-Trey, Konstanz, Germany) yardımı ile 15,20,25 …”
Section: Gereç Ve Yöntemunclassified
“…Bu sebeple fiber postların kök kırığı riskini azalttığı bildirilmiştir (18,19). Bu bilgiler doğrultusunda deneysel olarak dentin postlar hazırlanmış ve deneysel dentin postlarla yapılan çalışmalar başarılı sonuçlar vermiştir (20,21). Bu çalışmanın amacı, periodontal ligament taklit edilerek akrilik rezine gömülen köklere, kanal tedavisi yapıldıktan sonra farklı simantasyon materyalleri kullanılarak cam fiber post ve deneysel dentin post ile yapılan post-kor yapıların kırılma dirençlerini karşılaştırmaktır.…”
Section: Introductionunclassified